PENGARUH LATIHAN SPEED AND AGILITY (HOLLOW SPRINT WITH BALL) TERHADAP KETERAMPILAN MENGGIRING BOLA PADA PEMAIN SEPAK BOLA U-17 PSM FC PUJUD - Heriansyah, Dodo; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that the ability to dribble the players is still not optimal. The speed and agility of the athlete when dribbling is still not optimal, this can be seen when the athlete carries the ball is still not fast, so the ball is easily captured by the opponent. The purpose of this research was to determine the effect of Speed and agility (hollow sprint with ball) training on ball dribbling skills in the Existing PSM FC U-17 Soccer Players. The population in this research were 18-member PSM FC Pujud U-17 soccer players. The sampling technique used was total sampling or saturated samples so that the sample in this research amounted to 18 people. To determine the impact of speed and agility training (hollow sprint with ball), a test instrument was used, namely pree test and post test ball dribbling to measure ball dribbling skills in the PSM FC Under-17 soccer players. Then to prove the presence or absence of influence from the training provided, a significance test t or t test is performed. From the results of the calculation it is known that the value of tcount is 23,699 which is greater than the value of ttable which is 2,110. so that the alternative hypothesis is accepted, namely there is the influence of speed and agility (hollow sprint with ball) on dribbling skills in the U-17 PSM FC players. This shows that, the better the application of speed and agility (hollow sprint with ball), the better the dribbling skills of the PSM FC Under-17 soccer players.Key Words: Speed and agility training (hollow sprint with ball) dribbling skills